TINGKAT ADOPSI INOVASI BIOSECURITY AYAM RAS PETELUR DI KABUPATEN SIDRAP DAN FAKTORFAKTOR YANG MEMPENGARUHI - Rusni, Rusni (Teknosains: Media Informasi Sains dan Teknologi, 2015)
In order to encourage the adoption of innovations biosecurity at layer farmers, it requires an understanding of innovation adoption biosecurity layer and its influencing factors. This research aims to determine adoption of innovation level of biosecurity layer and its influencing factors. The Method is biosecurity weighting which consists of layer sources biosecurity, disrupt animal biosecurity, guests and workers biosecurity, sick animal biosecurity, feed biosecurity, waste biosecurity and egg crates biosecurity, while the adoption innovation influencing factors use infrensial statistics with test F and t test. The Results show the innovation adoption level of biosecurity layer are low in Sidrap on disrupt animal biosecurity as many as 59 people or 67.82%, guests and workers biosecurity consists of 59 people or 67.82%, while for the factors that influence the level of adoption of innovation is scale effort and behavior control. The conclusion is There are two factors that affect the level of adoption innovation layer in Sidrap, The first is The Enhancement of adoption innovation biosecurity can be started on a larger scale and the second is The ability to control his behavior.